Nutritional and sensory attributes of biscuits enriched with buckwheat - Tasnim Farzana; Fahiza Bisrat Hossain; Md Jaynal Abedin; Sadia Afrin; Shaikh Shahinur Rahman (Journal of Agriculture and Food Research, 2022)
Buckwheat is a promising food ingredient for the manufacture of different bakery foods because of its abundance of nutrients with health advantages, its gluten-free nature, and different polyphenol ingredients. In this study, buckwheat enriched biscuits (BEB) were formulated by blending wheat flour with buckwheat flour (BF) at the ratios of 100:0 (Control Biscuit), 90:10 (BEB-10), 80:20 (BEB-20), 70:30 (BEB-30), and 60:40 (BEB-40), and their nutrient, sensory, and microbiological analyses were investigated. The increment of buckwheat flour in formulated biscuits led to an increase in the mean protein, fat, fiber, and ash content, except carbohydrate. The iron, potassium, and zinc contents of the biscuits were also increased with the addition of buckwheat flour (BF). In terms of sensory evaluation, the overall acceptable scores for control biscuit (CB) and BEB-10, BEB-20, BEB-30, and BEB-40 were 7.56, 7.02, 6.98, 6.86, and 5.94, respectively. Therefore, BEB developed with up to 30% BF showed improved nutritional quality with acceptable sensory attributes. This study also concluded that BEB is microbiologically acceptable for up to six months.